2021
DOI: 10.3390/v13071322
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequence Analysis of Pseudorabies Virus Clinical Isolates from Pigs in China between 2012 and 2017 in China

Abstract: Pseudorabies virus (PRV) is an economically significant swine infectious agent. A PRV outbreak took place in China in 2011 with novel virulent variants. Although the association of viral genomic variability with pathogenicity is not fully confirmed, the knowledge concerning PRV genomic diversity and evolution is still limited. Here, we sequenced 54 genomes of novel PRV variants isolated in China from 2012 to 2017. Phylogenetic analysis revealed that China strains and US/Europe strains were classified into two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 70 publications
1
14
0
Order By: Relevance
“…Te PRV strain HeN21 was isolated from the tonsil of a 24-week-old pig that died from severe neuronal and respiratory signs in a PRV-outbreak farm in China in 2021; HuB20 and HBJZ-44-2021 were isolated from the lung and lymph node of two pigs with symptoms in two pig farms in Central China in 2020 and 2021, respectively; JSZL-2018 was isolated from the brain of a baby pig in Eastern China in 2018. Our previously collected PRV strains, including two variants (HuB1/ CHN2017 and SMX-2012) and two classical strains (Ea and Bartha-K61) [14], were also included as control viruses in this study. A total of 28 genome sequences downloaded from NCBI were used as reference genomes for bioinformatical analysis (Table S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Te PRV strain HeN21 was isolated from the tonsil of a 24-week-old pig that died from severe neuronal and respiratory signs in a PRV-outbreak farm in China in 2021; HuB20 and HBJZ-44-2021 were isolated from the lung and lymph node of two pigs with symptoms in two pig farms in Central China in 2020 and 2021, respectively; JSZL-2018 was isolated from the brain of a baby pig in Eastern China in 2018. Our previously collected PRV strains, including two variants (HuB1/ CHN2017 and SMX-2012) and two classical strains (Ea and Bartha-K61) [14], were also included as control viruses in this study. A total of 28 genome sequences downloaded from NCBI were used as reference genomes for bioinformatical analysis (Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Whole genome sequencing was performed as previously described [14]. Viral DNA was extracted using a commercial DNA/RNA extraction kit (Vazyme, Nanjing, China) and was checked for quality and quantity by agarose gel electrophoresis and using a Qubit ® 2.0 Fluorometer (Termo Scientifc, US).…”
Section: Whole Genome Sequencing and Bioinformatical Analysismentioning
confidence: 99%
“…Natural mutation-selection could contribute to the diversity changes in the PRV strains in genotype II. Positive selection has been detected in the amino acid residues at site 43/75/505/834/848/908/922 of gB, site 348/575/578 of gE, and site 59/75/194 of gC but not in gD [ 36 , 38 , 39 ]. In addition, site 929/934 of gB, site 495/540 of gE, and site 59/75/76/191 of gC are involved in the adaptive evolution after cross-species transmission.…”
Section: Genotyping and Variation In Prvmentioning
confidence: 99%
“…Consistently, it has been reported that SC is a recombinant strain between the Chinese early local PRV isolate and the vaccine strain Bartha-K61 [ 45 ]. In our recombination analysis based on 55 PRV genomes, a total of 23 recombination events were identified, with 16 events observed between Bartha-K61 and the Chinese strains [ 39 ]. The vaccine strain Bartha-K61 has been widely used to control porcine pseudorabies in China for decades.…”
Section: Genotyping and Variation In Prvmentioning
confidence: 99%
“…However, PRV variants emerged and spread in China since 2011, leading to huge economic losses ( An et al, 2013 ; Wu et al, 2013 ; Tong et al, 2015 ). Compared to classical virulent PRV, PRV variants were more pathogenic on pigs and commercial vaccines failed to provide complete protection against the variants ( Luo et al, 2014 ; Hu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%